Economic well-being induced empowerment through women’s savings groups: Evidence in the coastal fishing communities of Bangladesh - Rahman, M. Wakilur (Bangladesh Agricultural University, 2023)
Women’s empowerment becomes an important policy agenda and identifying pathways for empowerment is crucial for developing countries like Bangladesh specially to achieve SDGs. The prime objective of this paper was to examine whether community savings groups can truly improve the economic conditions of women, which may turn into women empowerment in fishing community or not. The propensity score matching and logistic regression technique was incorporated and required data were collected from Community Savings Groups (CSG) and nonCSG villages of coastal Bangladesh. Quantitative data were collected from 615 women comprising 306 CSG participants (intervention group) and 309 nonparticipants (control group). The results affirm CSG members were economically more solvent and less dependent on borrowed money compared to the members of non-CSG. Improved economic indicators (savings, income and expenditure) of CSG households were the foundation of attaining women empowerment of the intervention group. The women who were CSG members performed better in various dimensions of leadership capacity than those in the non-CSG women. Econometric analysis confirmed the positive impacts of CSG interventions on savings, gross household income, earning from catching fish, alternative income-generating activities (AIGAs), expenditure, and women empowerment. The initiatives of CSG not only generate economic well-being but also contribute to women’s empowerment. Financial access and literacy, along with an enabling environment for productive engagement of women, reduced gender inequality in the fishing community. Establishing institutional linkages (advisory and financial), legality/registration of CSGs from the government authority, and facilitation of AIGAs are crucial for sustaining the benefits.